Femicide across Europe : theory, research and prevention - Ṿail, Shalṿah; Corradi, Consuelo, 1955-; Naudi, Marceline (Policy Press shorts. Policy & practice., 2018)
This book is the first on femicide in Europe and presents the findings of a 4 year project discussing various aspects of femicide. It looks at the prevention programmes and comparative quantitative and qualitative data collection, as well as the impact of culture. It proposes the establishment of an European Observatory on Femicide.